Aerosol water content enhancement leads to changes in the major formation mechanisms of nitrate and secondary organic aerosols in winter over the North China Plain. (15th October 2021) - Chen, Chunrong; Zhang, Haixu; Yan, Weijia; Wu, Nana; Zhang, Qiang; He, Kebin
Abstract: In recent years, severe air pollution still frequently occurs in winter despite the effective implementation of clean air actions in China. Therefore, field measurements of particle composition and gas precursors were collected from December 1, 2018 to January 15, 2019 at an urban site in a central Chinese city to investigate the existing mechanisms of pollution. The hourly averaged PM2.5 concentration during the campaign was 92.7 μg m −3, with nitrate and organic aerosol (OA) demonstrated as the principal components. Generally, NO2 oxidation in the daytime was observed as the major mechanism for nitrate generation, and aerosol water content (AWC) showed its influential role with the associated increases in the nitrogen oxidation and nitrate partitioning ratios. When AWC increased from dozens to hundreds of μg m −3 after the afternoon, nocturnal N2 O5 hydrolysis was demonstrated as the overriding mechanism and provoked extreme contamination of nitrates. Five sources of organic aerosols (OAs) were identified: hydrocarbon-like OAs (HOAs, 16.5%), coal combustion OAs (CCOAs, 19.2%), biomass burning OAs (BBOAs, 9.9%), semi-volatile oxygenated OAs (SV–OOAs, 29.4%), and low-volatile oxygenated OAs (LV-OOAs, 25.0%). SV-OOAs and LV-OOAs were identified as gasSOAs and aqSOAs according to their sensitivities to the atmospheric oxidation capacity and AWC. In addition, aqueous-phase processing was found to be the dominant pathway for SOA formation when the AWC concentration was higher than 80 μg m −3 . As an influential factor for nitrate and SOA formation, AWC could be greatly affected by RH and the concentrations of inorganic species. Sulfate, which was mainly contributed by anthropogenic emissions, was demonstrated to be a significant factor for active aqueous phase reactions, although SO2 has been dramatically reduced in recent years. Above all, this study revealed the significant role of AWC in current pollution episode in winter, and will assist in establishing future measures for pollution mitigation. Graphical abstract: Image 1 Highlights: National anthropogenic emissions of SO2 and NOx have been reduced in recent years. Nitrate and OA were the principal components in the particles. High aerosol water content would result in nitrate pollution via N2 O5 hydrolysis. Aqueous-phase reactions was the dominant pathway for SOA formation with high AWC. Sulfate was sensitive to AWC and acted as the main cause for AWC enhancement.